Analisis Vegetasi Tegakan Pohon Di Kawasan Hutan Kota Bukit Langkisau Painan, Pesisir Selatan - Chairul Chairul; lola sutra islami arwin (Jurnal Biologi Universitas Andalas, 2023)
Urban forest management must adapt to urban development and aspects of urban life so that the availability and management of key lands in the development of urban forests and the presence of vegetation as the driving element, one of which is trees. This study aims to determine the composition and structure of tree stands in the Bukit Langkisau Painan City Forest, Pesisir Selatan. The method used was purposive sampling with a plot size of 20 m x 60 m with a sub plot of 10 x 10 m for level 12 plots of trees each. It was found that the vegetation composition of tree stands were 10 families, 12 genera, 13 species, and 27 individuals with the dominant family Myrtaceae and the co-dominant families Meliaceae, and sapindaceae. The highest significance value was found in Syzygium racemosum with a value of 43.399 % and the lowest significance index was found in the species Xerospermum noronhianum with 9.298 %. The diversity index (H') is 2,439 which indicates that species diversity classified to moderate. Keyword: bukit langkisau, composition, structure, urban fores.